Adjuvant chemotherapy for breast cancer - Senkus-Konefka, Elżbieta; Wełnicka-Jaśkiewicz, Marzena (Contemporary Oncology/Współczesna Onkologia, 2002)
Systemic adjuvant chemotherapy for early breast cancer has been used routinely for over 30 years. Over these years both the indications, and treatment schemes have been frequently modified and updated. As a result of improvements of breast cancer care, including adjuvant chemotherapy, a decrease in breast cancer mortality has been observed in some developed countries since 1980. The 1998 metaanalysis of the Early Breast Cancer Trialists' Cooperative Group, which included over 18000 patients in over 40 randomized trials of adjuvant chemotherapy demonstrated improvement in both overall survival and progression-free survival in all subgroups of patients. This improvement was independent of N-stage, menopausal status or steroid receptor status. It was also found that chemotherapy offers additional benefit in patients with hormone-sensitive tumors treated with adjuvant hormonal therapy. These data, as well as the results of earlier studies were reflected in modification of risk subgroups definition and broadening of indications for adjuvant systemic treatment. According to current standards, adjuvant therapy can be avoided only in best prognostic subgroups, i. e. in patients older than 35 years, with low-grade, steroid-receptor positive tumors of less than 2 cm of diameter and negative regional lymph-nodes, in whom risks and toxic effects of chemotherapy outweigh the benefit of treatment. Two consensus statements: European and American, were developed over the last two years, regarding the indications for systemic adjuvant treatment in early breast cancer. Further development is observed in the knowledge of patient- and tumour-related prognostic and predictive factors, allowing for continuous refinements in treatment selection. Anthracycline-based regimens were demonstrated to have superior activity as compared to standard cyclophosphamide - methotrexate - 5-fluorouracil regimen and are gaining wider popularity in the adjuvant treatment. The results of treatment may also be influenced by the timing of chemotherapy and its dose intensity. The role of taxanes, high-dose chemotherapy with stem-cell support or monoclonal antibodies in adjuvant setting, as well as optimal way of combining chemotherapy with new classes of drugs used in hormonal therapy is unknown; the use of these strategies is currently a subject of clinical studies.